Effect of Tunneling Incentive, Bonus Mechanism, Debt Covenant and Independent Board of Commissioners Regarding Transfer Pricing - Abbas, Dirvi Surya; Kismanah, Imas; Karmila, Dinar; Kunah, Kunah; Ulfiah, Ulfiah (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to ascertain the impact of the Independent Board of Commissioners, bonus system, debt covenant, and tunneling incentive on transfer pricing in consumer products companies listed on the Indonesia Stock Exchange (IDX). Five years, specifically the years 2016–2020, were employed for the research. All consumer goods companies registered the study's participants include those who traded on the Indonesia Stock Exchange (IDX) between 2016 and 2020. Purposive sampling was employed in the sampling procedure. Ten businesses were selected based on preset standards. secondary information from the website of the Indonesia Stock Exchange is the kind of data that was used. The analysis method used is panel data regression analysis. The findings demonstrated that the Independent Board of Commissioners, Bonus Mechanism, and Tunneling Incentive Debt Covenant has no impact on Transfer Pricing, although it does have an impact.